2022
DOI: 10.3390/aerospace9030151
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcations of Periodic Orbits in the Gravitational Field of Irregular Bodies: Applications to Bennu and Steins

Abstract: We investigate the topological types and bifurcations of periodic orbits in the gravitational field of irregular bodies by the well-known two parameter analysis method. Results show that the topological types of periodic orbits are determined by the locations of these two parameters and that the bifurcation types correspond to their variation paths in the plane. Several new paths corresponding to doubling period bifurcations, tangent bifurcations and Neimark–Sacker bifurcations are discovered. Then, applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The bifurcation of periodic orbit families helps locate points of extrema along the periodic orbit family with respect to the period or energy; such kinds of bifurcations are called first-kind bifurcations. The first kind of bifurcation of periodic orbit families around asteroids has been well studied in the literature [25][26][27]. Ni et al showed that multiple first-kind bifurcations occur along a periodic orbit family around an asteroid [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bifurcation of periodic orbit families helps locate points of extrema along the periodic orbit family with respect to the period or energy; such kinds of bifurcations are called first-kind bifurcations. The first kind of bifurcation of periodic orbit families around asteroids has been well studied in the literature [25][26][27]. Ni et al showed that multiple first-kind bifurcations occur along a periodic orbit family around an asteroid [28].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the literature has paid little attention to period-multiplying bifurcations around asteroids. Liu et al were able to locate period-doubling bifurcations around asteroids Bennu and Steins [26]. Brown and Scheeres located and computed period-multiplying bifurcations up to integer five around the asteroid Bennu [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation